DNA Methylation Patterns of a Satellite Non-coding Sequence – FA-SAT in Cancer Cells: Its Expression Cannot Be Explained Solely by DNA Methylation - Ferreira, Daniela; Escudeiro, Ana; Adega, Filomena; Chaves, Raquel (Frontiers in Genetics, 2019)
Satellite ncRNAs are emerging as key players in cell and cancer pathways. Cancer-linked satellite DNA hypomethylation seems to be responsible for the overexpression of satellite non-coding DNAs in several tumors. FA-SAT is the major satellite DNA of Felis catus and recently, its presence and transcription was described across Bilateria genomes. This satellite DNA is GC-rich and includes a CpG island, what is suggestive of transcription regulation via DNA methylation. In this work, it was studied for the first time the FA-SAT methylation profile in cat primary cells, in four passages of the cat tumor cell line FkMTp and in eight feline mammary tumors and the respective disease-free tissues. Contrary to what was expected, we found that in most of the tumor samples analyzed, FA-SAT DNA was not hypomethylated. Furthermore, in these samples the transcription of FA-SAT does not correlate with the methylation status. The use of a global demethylating agent, 5-Azacytidine, in cat primary cells caused an increase in the FA-SAT non-coding RNA levels. However, global demethylation in the tumor FkMTp cells only resulted in the increased levels of the FA-SAT small RNA fraction. Our data suggests that DNA methylation of FA-SAT is involved in the regulation of this satellite DNA, however, other mechanisms are certainly contributing to the transcriptional status of the sequence, specifically in cancer.